Biomimetic collagen/elastin meshes for ventral hernia repair in a rat model. (1st March 2017) - Minardi, Silvia; Taraballi, Francesca; Wang, Xin; Cabrera, Fernando J.; Van Eps, Jeffrey L.; Robbins, Andrew B.; Sandri, Monica; Moreno, Michael R.; Weiner, Bradley K.; Tasciotti, Ennio
Graphical abstract: Abstract: Ventral hernia repair remains a major clinical need. Herein, we formulated a type I collagen/elastin crosslinked blend (CollE) for the fabrication of biomimetic meshes for ventral hernia repair. To evaluate the effect of architecture on the performance of the implants, CollE was formulated both as flat sheets (CollE Sheets) and porous scaffolds (CollE Scaffolds). The morphology, hydrophylicity and in vitro degradation were assessed by SEM, water contact angle and differential scanning calorimetry, respectively. The stiffness of the meshes was determined using a constant stretch rate uniaxial tensile test, and compared to that of native tissue. CollE Sheets and Scaffolds were tested in vitro with human bone marrow-derived mesenchymal stem cells (h-BM-MSC), and finally implanted in a rat ventral hernia model. Neovascularization and tissue regeneration within the implants was evaluated at 6 weeks, by histology, immunofluorescence, and q-PCR. It was found that CollE Sheets and Scaffolds were not only biomechanically sturdy enough to provide immediate repair of the hernia defect, but also promoted tissue restoration in only 6 weeks. In fact, the presence of elastin enhanced the neovascularization in both sheets and scaffolds. Overall, CollE Scaffolds displayed mechanical properties more closely resembling those of native tissue, and induced higher gene expression of the entire marker genes tested, associated with de novo matrix deposition, angiogenesis, adipogenesis and skeletal muscles, compared to CollE Sheets. Altogether, this data suggests that the improved mechanical properties and bioactivity of CollE Sheets and Scaffolds make them valuable candidates for applications of ventral hernia repair. Statement of Significance: Due to the elevated annual number of ventral hernia repair in the US, the lack of successful grafts, the design of innovative biomimetic meshes has become a prime focus in tissue engineering, to promote the repair of the abdominal wall, avoid recurrence. Our meshes (CollE Sheets and Scaffolds) not only showed promising mechanical performance, but also allowed for an efficient neovascularization, resulting in new adipose and muscle tissue formation within the implant, in only 6 weeks. In addition, our meshes allowed for the use of the same surgical procedure utilized in clinical practice, with the commercially available grafts. This study represents a significant step in the design of bioactive acellular off-the-shelf biomimetic meshes for ventral hernia repair.